A Case Study of Excreta Disposal Following the 2006 Java Earthquake* - Pean, Thye Yoke; Effendi, Agus Jatnika; Soewondo, Prayatni; Brdjanovic, Damir; Setiadi, Tjandra (ITB Journal Publisher, LPPM ITB, 2015)
Providing safe excreta disposal following disasters is important for disease prevention and the safety and dignity of the affected population. This is challenging because every emergency varies due to the nature of the disaster, local conditions and the characteristics of the affected population. This paper investigates the impact of the 2006 Java earthquake on excreta disposal needs and the response to those needs. Relevant documents were retrieved from the ReliefWeb database, complemented by a literature search. The case study highlights gaps in rapidly providing latrines on a large scale. Three months after the disaster, only 57% of the latrines targeted had been provided. One way to address this problem is to better understand the factors affecting excreta disposal needs and response, allowing appropriate solutions to be identified more effectively.